(untitled) (Journal of Pharmaceutical Negative Results, 2022)
n freshwater ecosystems water quality plays an important role in determining the status and condition of that freshwater ecosystem. The present limnological investigations include analysis of various physico chemical parameters at the selected sites of Vikram Tearth Sarovar Ujjain (M.P) from Jan 2019 to Dec 2019. The aim of the current study was to evaluate the pollution status of Vikram Tearth Sarovar on the basis of different physico chemical conditions. The mean air temperature ranged from 29.0 ℃  3.1 tominimum 20.1℃  4.3. The pH of the selected water body was alkaline throughout the study period. The pond depicted the usual cation progression Ca>Mg. The pond was categorized as Calcium rich after Ohle (1934). The water in Vikram Tearth Sarovar was transparent during winters rest it was turbid throughout the study period during all the seasons. The Water in Vikram Tearth Sarovar was typically hard water type. The DO (3.8 0.2) was minimum during summers. High mean values of Nitrate (7.2891.86) andPhosphate (1.1100.1) were recorded during summers. The mean BOD (12.90.1) in Vikram Tearth Sarovar was maximum during summer season. Stastical analysis was also carried out to find the degree of relationship between various abiotic factors. D.O showed Negative correlation with Temperature (-0.892), BOD(-0.961), Nitrate (-0.896) and Phosphate (-0.943). While as Temperature showed positive correlation with BOD (0.877), Total Hardness (0.752), Magnesium Hardness (0.912), Nitrate(0.902) and Phosphate (0.889). The high values of the physico chemical properties of water were recorded in the present study in Vikram Tearth Sarovar Ujjain indicating the eutrophic nature of the pond due to increased anthropogenic activities. Thus measures need to be enforced to reduce the rate of pollution of the selected water body arising from the anthropogenic activities in the catchment of the reservoir.